2021
DOI: 10.1038/s41560-021-00783-z
|View full text |Cite
|
Sign up to set email alerts
|

Tailoring electrolyte solvation for Li metal batteries cycled at ultra-low temperature

Abstract: Lithium metal batteries (LMBs) hold the promise to pushing cell level energy densities beyond 300 Wh kg −1 while operating at ultra-low temperatures (< −30°C). Batteries capable of both charging and discharging at these temperature extremes are highly desirable due to their inherent reduction of external warming requirements. Here we demonstrate that the local solvation structure of the electrolyte defines the charge-transfer behavior at ultra-low temperature, which is crucial for achiev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

18
502
1
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 501 publications
(563 citation statements)
references
References 57 publications
18
502
1
1
Order By: Relevance
“…[ 57 , 58 , 59 , 60 ] These uniform and rapid Li ion diffusion on this advanced, orderly, and robust SEI contribute to sustain enough mass transport of Li ions near the electrolyte–electrode interface, and the homogeneous Li depositions can be obtained. [ 61 , 62 , 63 ] This SEI is smooth and has high mechanical strength, ensuring effective improvements of the electrode reversibility, interface stability, and uniformity of Li deposition. Thus, an ultrastable dendrite‐free deposition of homogeneous ALi is effectively regulated on this advanced, multilayer‐ordered, and robust SEI for a more robust ALi cluster anode.…”
Section: Resultsmentioning
confidence: 99%
“…[ 57 , 58 , 59 , 60 ] These uniform and rapid Li ion diffusion on this advanced, orderly, and robust SEI contribute to sustain enough mass transport of Li ions near the electrolyte–electrode interface, and the homogeneous Li depositions can be obtained. [ 61 , 62 , 63 ] This SEI is smooth and has high mechanical strength, ensuring effective improvements of the electrode reversibility, interface stability, and uniformity of Li deposition. Thus, an ultrastable dendrite‐free deposition of homogeneous ALi is effectively regulated on this advanced, multilayer‐ordered, and robust SEI for a more robust ALi cluster anode.…”
Section: Resultsmentioning
confidence: 99%
“…In contrast, it has demonstrated that the solvation structure of the electrolyte deeply affects the charge-transfer behavior at low temperature. [25] The performance was mainly influenced by the interfacial ion desolvation mechanics and the corresponding Li deposition morphologies. Finally, the LMBs are able to improve the Columbic efficiency with decreasing dendritic growth.…”
Section: Ether Electrolytesmentioning
confidence: 99%
“…Low-temperature performance loss of graphite-based LIBs is an issue that researchers are pursuing to address all the time. [5,12] Thel imited charge capacity of LIBs (or discharge capacity of graphite) at subzero temperature is mainly attributed to as luggish desolvation process at the graphite interphase,the dominant impedance contributor. [7,12] Therefore,u tilizing co-intercalation of solvents is undoubtedly astraightforward way to circumvent such abig obstacle.…”
Section: Methodsmentioning
confidence: 99%
“…[5,12] Thel imited charge capacity of LIBs (or discharge capacity of graphite) at subzero temperature is mainly attributed to as luggish desolvation process at the graphite interphase,the dominant impedance contributor. [7,12] Therefore,u tilizing co-intercalation of solvents is undoubtedly astraightforward way to circumvent such abig obstacle. To prove the strategy,t he low-temperature operation of the AG anode with Na + -ether co-intercalation mechanism is further investigated, whose capacity maintains 50 %a t 0.1 Ag À1 (1C-rate) and 43 %w ith 0.3 Ag À1 at À40 8 8Cw hen compared to the capacity at 25 8 8C(Figure S16).…”
Section: Methodsmentioning
confidence: 99%